A smart tailor-made G-clip reporter for sensitive detection of G-triplet-containing sequences1. Issue 10 (21st May 2015) - Cai, Liang-Yuan; Nie, Ji; Zhang, Yi-Wei; Zhang, Fang-Ting; Zhou, Ying-Lin; Zhang, Xin-Xiang
<x xml:space="preserve">Abstract</x> A smart tailor-made G-clip reporter is developed for sensitive detection of a target sequence containing a G triplet.